Crossing Boundaries in Early Judaism and Christianity : Essays in Honor of Alan F. Segal. - Stratton, Kimberley. (Supplements to the Journal for the Study of Judaism, 2016)
This volume celebrates the scholarship of Alan Segal. During his prolific career, Alan published ground-breaking studies that shifted scholarly conversations about Christianity, rabbinic Judaism, Hellenism and Gnosticism. Like the subjects of his research, Alan crossed many boundaries. He understood that religions do not operate in academically defined silos, but in complex societies populated by complicated human beings. Alan's work engaged with a variety of social-scientific theories that illuminated ancient sources and enabled him to reveal new angles on familiar material. This interdisciplinary approach enabled Alan to propose often controversial theories about Jewish and Christian origins. A new generation of scholars has been nurtured on this approach and the fields of early Judaism and Christianity emerge radically redefined as a result.